Facilitating Qur'anic Literacy in Early Childhood through Smart Hafiz “Al Qolam” - Taufikin, Taufikin (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
The introduction of Qur'anic literacy from an early age is necessary in contemporary Islamic education. However, conventional approaches to teaching Qur'anic literacy often face various limitations, especially in maintaining children's interest in learning. This study examines the effectiveness of Smart Hafidz